2021
DOI: 10.3390/antibiotics10040461
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Active Chimeric Lysin with a Calcium-Enhanced Bactericidal Activity against Staphylococcus aureus In Vitro and In Vivo

Abstract: Lysins, including chimeric lysins, have recently been explored as novel promising alternatives to failing antibiotics in treating multi-drug resistant (MDR) pathogens, including methicillin-resistant Staphylococcus aureus (MRSA). Herein, by fusing the CHAP (cysteine, histidine-dependent amidohydrolase/peptidase) catalytic domain from the Ply187 lysin with the non-SH3b cell-wall binding domain from the LysSA97 lysin, a new chimeric lysin ClyC was constructed with Ca2+-enhanced bactericidal activity against all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 44 publications
(47 reference statements)
1
17
0
Order By: Relevance
“…Researchers had demonstrated a synergetic approach to bacterial treatment by a combination of endolysin and antibiotics (Daniel et al, 2010;Letrado et al, 2018). In our previous studies, we showed that penicillin G and ClyC had a synergistic effect, reducing the MIC of ClyC for planktonic and sessile S. aureus (Li et al, 2021). It was beneficial to reduce the working concentration of ClyC in the lesion and weaken potential safety hazards.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Researchers had demonstrated a synergetic approach to bacterial treatment by a combination of endolysin and antibiotics (Daniel et al, 2010;Letrado et al, 2018). In our previous studies, we showed that penicillin G and ClyC had a synergistic effect, reducing the MIC of ClyC for planktonic and sessile S. aureus (Li et al, 2021). It was beneficial to reduce the working concentration of ClyC in the lesion and weaken potential safety hazards.…”
Section: Discussionmentioning
confidence: 94%
“…The chimeric lysin, ClyC, was expressed as described previously (Li et al, 2021). Concentration of ClyC was determined by BCA assay and visualized by SDS-PAGE.…”
Section: Preparation Of Clyc-ahmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasmid constructs and protein purification procedures were performed as in our previous studies ( Huang et al, 2015 ; Yang et al, 2017 ; Li et al, 2021 ). Briefly, E. coli BL21(DE3) cells with their plasmids were grown in LB medium supplemented with 50 μg/mL kanamycin at 37°C 160 rpm to an OD600 of 0.4∼0.6.…”
Section: Methodsmentioning
confidence: 99%
“…For example, by fusing the CD of lysin Ply187 with the CBD of PlySs2, a novel chimeric lysin, ClyF, with increased thermostability, pH tolerance, and antibacterial activity against both planktonic and biofilm MRSA was formed ( Yang et al, 2017 ). Similarly, ClyC, a novel chimeric lysin with increased bactericidal activity against S. aureus strains and its biofilms, including MRSA, in the presence of calcium ions was formed by fusing the CD of lysin Ply187 with the CBD of LysSA97 ( Li et al, 2021 ). Despite the successful engineering of chimeric lysis, questions still remain such as how the lysins interact with the biofilms and if different CDs and CBDs could affect the ability of lysins to remove biofilms.…”
Section: Introductionmentioning
confidence: 99%